Iloilo CODE NGO's experience in the advancement of nine (9) Barangay Development Councils in the municipality of Batad, Iloilo ; 1997-2002. - Llorca, Andrew Raymund G.
The study Iloilo CODE NGOs Experience in the Advancement of Nine(9) Barangay Develoment Councils in the Municipality of Batad; 1997-2002, is an analysis of NGO involvement and participation in the local public administration process of nine (9) selected barangays in the municiplaity of Batad. Specifically, their involvement is through the "Development of Institutional Mechanisms for Participatory Local Governance through the Strenthening of Barangay Development Councils (BDCs)" program. The activities that were involved during their intervention explore the parameters or Key Result Areas that they instituted and spearheaded in their project sites, whether they were successful in inculcating to the barangay leaders and local civil society organizations who are members of the BDCs, and people's participation from the residents of the community, the importance of NGO-LGU collaboration in formulating and deliberating programs and activities that really address the real interests of the people in bringing about genuine development. Findings and learnings from the experience as through the perceptions and views of respondents in this study showed that Iloilo Iloilo CODE NGOs was successful in increasing the critical awareness of the participants of the participatory local governance processes especially their rights, roles, functions and obligations and the mechanisms and processes involved in barangay administration. However, continued intervention is still needed as most target beneficiaries still lack technical expertise to conduct these activities on their own.